2020
DOI: 10.1136/jclinpath-2020-206611
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of CD47 expression in hepatocellular carcinoma

Abstract: AimsCD47 is upregulated on the surface of various tumour cells, and it is known to inhibit the phagocytosis of tumour cells by macrophages. Immunotherapy that targets CD47 has demonstrated success in preclinical trials and is now under clinical investigation for both solid and haematological malignancies. However, data regarding CD47 expression in hepatocellular carcinoma (HCC) tissue and its correlation with clinical outcomes in patients with HCC remain limited. Here, we investigated the clinicopathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Several clinical trials on CD47-targeting agents are ongoing that have shown promising results ( Chester et al, 2015 ; Liu et al, 2015 ). Kim et al demonstrated that CD47 is upregulated in HCC tumor tissues and correlated with shorter recurrence-free survival ( Kim et al, 2021 ). The differences in PD-1 and CD47 expression between the clusters and normal and tumor samples were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical trials on CD47-targeting agents are ongoing that have shown promising results ( Chester et al, 2015 ; Liu et al, 2015 ). Kim et al demonstrated that CD47 is upregulated in HCC tumor tissues and correlated with shorter recurrence-free survival ( Kim et al, 2021 ). The differences in PD-1 and CD47 expression between the clusters and normal and tumor samples were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Adopting a similar behavior, cancer cells overexpress CD47 to escape M1 macrophage innate immune response by binding to their SIRPĪ± ligand. Increased expression of CD47 has been documented in hematological malignancies and also in various human solid tumors [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Restoring the innate macrophage immunity by targeting the CD47/SIRPĪ± axis is under intense preclinical and clinical evaluation [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression patterns of CD47 in human malignancies have been investigated in a small number of published studies, mainly from Eastern Institutes. Association with aggressive clinical behavior and poor prognosis have been reported in breast [ 5 ], esophageal [ 6 ] and gastric cancer [ 7 ], as well as hepatomas [ 8 ], and melanomas [ 9 ]. In non-small cell lung cancer (NSCLC), contradictory results have been published in four reports [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of CD47 to its receptor signal regulatory protein a (SIRPa) on macrophages inhibits phagocytosis activation and can contribute to tumor formation [113,114]. CD47 is therefore overexpressed on various hematologic and solid tumors to evade the cellular immune response, including HCC where it is also associated to poorer outcome [21]. Consequently, blocking CD47-signaling inhibited growth of HCC models and restored sensitivity to chemotherapy [115].…”
Section: Cd47-sirpamentioning
confidence: 99%
“…In the context of human cancer therapy, the currently most studied ICIs are PD1 (programmed cell death protein 1), CTLA-4 (cytotoxic T lymphocyte protein 4), LAG-3 (lymphocyte activation gene 3 protein), and, TIM-3 (T cell immunoglobulin and mucin-domain containing)-for an overview including the respective ligands, see also Figure 2. [16][17][18][19][20][21][22]. Abbreviations: APC, antigen-presenting cell;…”
Section: Introductionmentioning
confidence: 99%